Optimization of Career Services in Improving Student Success in Received at State Universities - Riana Wulanningrum; Budi Haryanto; Renny Oktafia (Proceedings of The ICECRS, 2020)
Schools generally prepare class XII students to continue their studies at the higher education level, both official and non-official, this is done because almost 90% more high school students choose to continue their studies in higher education. In general, students take two selection courses at tertiary institutions, namely the national selection of state tertiary institutions (SNMPTN) and the joint selection of state tertiary institutions (SBMPTN). Both of these selections require intense preparation and guidance by the school conducted by the homeroom teacher and tutor. The purpose of this study is to find out whether the optimization of career services can improve the success of students who are accepted into state universities. This study uses qualitative methods, namely research procedures that produce descriptive data in the form of written or oral words from people or observable behavior. The study was conducted at SMA Muhammadiyah 2 Sidoarjo. In this study the source of the data obtained from interviews and observations to counseling guidance teachers, vice principals in the field of student affairs, public relations and school principals. Research data uses alumni data from Muhammadiyah 2 Sidoarjo High School from the 2015-2016 academic year until 2019 - 2020. Guidance and counseling have a very important role in helping the achievement of national education goals, and helping students achieve maximum potential development, independence in their lives, and decision making and choices to create a productive, prosperous and caring public welfare life.